Development of a stated-preference instrument to prioritize treatment goals in recent onset schizophrenia. (2nd December 2017) - Beusterien, Kathleen; Chan, Elcie; Such, Pedro; de Jong Laird, Anne; Heres, Stephan; Amos, Kaitlan; Loze, Jean-Yves; Nylander, Anna-Greta; Robinson, Paul; Bridges, John F. P.
Abstract: Objective: This study sought to evaluate a new stated-preference instrument to prioritize multiple treatment goals among people with recent onset schizophrenia. Methods: A draft survey instrument was developed to assess preferences for 13 key treatment goals that were identified based on the literature. The survey incorporates best–worst scaling (BWS), which shows repeated subsets comprising 4 of the 13 goals, and respondents identify which is most important and which is least important to them. Pre-test interviews were conducted in the UK, Italy, and Germany among people aged 18 to 35 diagnosed with schizophrenia within the past 5 years. Specifically, participants completed the instrument online in their native language, followed by a telephone interview to provide feedback on the clarity, relevance, and comprehensiveness of the survey. The interview data were analyzed to assess interpretation and content validity of the survey. Results: Fifteen participants (five per country) provided feedback (mean age = 31; 60% male). Feedback was comparable across countries and confirmed that the key treatment goals assessed were relevant and meaningful. Probing by interviewers ascertained that respondents interpreted the questions appropriately and identified the treatment goals that were most and least important to them. Based on the characterization of the goals, a conceptual model was developed illustrating hypothesized associations among them. Conclusion: The results confirm that the BWS methodology and key treatment goals in this new instrument are appropriate for use in recent onset schizophrenia. These results will help guide measurement of patient-relevant endpoints in future studies.